Dengue Encephalitis with ‘Double Doughnut Sign’ – A Rare Case Report (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Dengue fever is one of the most common arboviral infections, and it is the world’s fastest-spreading tropical illness. According to the World Health Organization, fifty million cases of clinical dengue infections occur each year, posing a significant public health hazard, primarily in Southeast Asia and the Western Pacific. The clinical spectrum of dengue fever ranges from asymptomatic infection to dengue shock syndrome. Although dengue virus is non-neurotropic virus, there is increasing evidence for dengue viral neurotropism suggesting there may be an element of direct viral encephalitis. Encephalopathy has been thought to result from the multisystem derangement that occurs in severe dengue, with liver failure, shock and coagulopathy causing a cerebral insult.  Dengue encephalitis is a rare disease. We report dengue encephalitis in a 55-year-old female, admitted in Rajshahi Medical College Hospital, Rajshahi, Bangladesh who presented with fever, vomiting, and altered level of consciousness. Her serum dengue NS1 was positive. MRI of brain showed hyperintensity in both basal ganglia & cerebellar region, which is identical to “Double Doughnut sign” found specifically in dengue encephalitis.J Bangladesh Coll Phys Surg 2023; 41: 96-98